L02 Insulin sensitivity and early-phase insulin secretion in normoglycemic patients with huntington's disease. (29th August 2012) - Russo, CV; Salvatore, E; Tucci, T; Rinaldi, C; Massarelli, M; Sorrentino, P; Rossi, F; Maio, LD; Filla, A; Colao, A; De Michele, G
Abstract : Background: Huntington's Disease (HD) is an autosomal dominant neurodegenerative disorder caused by an expanded CAG repeat in exon 1 of the HTT gene. Apart from neurological impairment, there is increasing evidence pointing towards an early involvement of the endocrine system in HD. Recent studies, conducted to investigate the association with increased risk of diabetes mellitus and with impairment in insulin sensitivity and secretion in HD patients, led to contradictory results. Aims: To investigate glucose homeostasis in HD by performing an oral glucose-tolerance test (OGTT) to evaluate the glucose-tolerance status and OGTT-related insulin release. Patients and Methods: Twenty-eight consecutive patients with HD and 28 healthy controls were matched for age, sex, and BMI. Diagnosis of HD was confirmed in all patients by analysis for the CAG repeat expansion. Clinical assessment of patients was performed using the Unified Huntington's Disease Rating Scale (UHDRS) motor section and the Total Function Capacity (TFC). Wide basal metabolic investigations and a 2 h 75-g OGTT were performed. We used the homeostasis model assessment of insulin resistance (HOMA-IR) as index of insulin sensitivity. Insulin secretion was determined by the insulinogenic index. Results: HD patients did not differ from the control group with respect to fasting plasma glucose level, insulin sensitivity and secretion. However, in comparison with controls HD patients showed lower serum glucose (−19%) and insulin levels (−48%) 30 min. after oral glucose load and higher serum insulin levels at 90 (+132%) and 120 min. (+380%). CAG expansion size, disease stage, or BMI did not influence HOMA-IR and insulinogenic index in HD patients. Conclusions: Our data challenge the assumption of an increased risk of diabetes among HD patients although they suggest abnormal glucose regulation.